Pratiques d'une métropole émergente par les usagers des transports en commun, le cas du Cap, Afrique du Sud - Solène Baffi (EchoGéo)
The city of Cape Town, like other cities in South Africa, is developing towards the dual model of the post-apartheid city and the emerging city. This evolution involves important demographic changes, as well as social and political. Those changes are especially visible in the urban space due to the spatial mismatch which still characterizes the city and keeps on isolating township dwellers from benefiting the city's opportunities, especially in terms of labour. It results in long and fastidious mobilities for low-income populations, whereas the transport system is still largely inherited from the apartheid era. The study of the maids' mobilities enables to enlighten these socio-spatial changes, especially through the observation of their practice of the transport network, the strategies they adopt to move and through their experience of the transport space.